2015
DOI: 10.5455/medarh.2015.69.77-80
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Outcome Prognosis in Septic and Non-septic Acute Kidney Injury Patients

Abstract: Aim:The objective of this study was to evaluate prognostic impact of clinical factors on outcome of renal function in septic and non-septic acute kidney injury (AKI) patients.Methods:The prospective, observational, clinical study was performed at Nephrology Clinic and Clinic for Infectious Diseases, University Clinical Centre Sarajevo. One hundred patients with diagnosis of AKI were enrolled in the study, and divided into two groups: septic and non-septic AKI patients. Clinical parameters included causes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As for AKI diagnostic criteria, six studies used the RIFLE criteria [ 80 , 101 105 ]; the remaining three studies [ 100 , 106 , 107 ] were published before the RIFLE criteria were proposed. Percentages of patients by RIFLE criteria severity were listed in four studies [ 80 , 101 , 102 , 104 ]; Risk was the most common level of severity in one study [ 102 ], while Injury was the most common in two studies [ 80 , 101 ], and Failure was the most common in one study [ 104 ]. Causes of sepsis were demonstrated in two studies [ 101 , 103 ]; in these studies, sepsis was caused by intrathoracic infections (such as pneumonia) and intra-abdominal infections in approximately 30 and 25% of cases, respectively, thus accounting for more than half of all cases.…”
Section: Commentarymentioning
confidence: 99%
“…As for AKI diagnostic criteria, six studies used the RIFLE criteria [ 80 , 101 105 ]; the remaining three studies [ 100 , 106 , 107 ] were published before the RIFLE criteria were proposed. Percentages of patients by RIFLE criteria severity were listed in four studies [ 80 , 101 , 102 , 104 ]; Risk was the most common level of severity in one study [ 102 ], while Injury was the most common in two studies [ 80 , 101 ], and Failure was the most common in one study [ 104 ]. Causes of sepsis were demonstrated in two studies [ 101 , 103 ]; in these studies, sepsis was caused by intrathoracic infections (such as pneumonia) and intra-abdominal infections in approximately 30 and 25% of cases, respectively, thus accounting for more than half of all cases.…”
Section: Commentarymentioning
confidence: 99%
“…As for AKI diagnostic criteria, six studies used the RIFLE criteria [ 78 , 99 103 ]; the remaining three studies [ 98 , 104 , 105 ] were published before the RIFLE criteria were proposed. Percentages of patients by RIFLE criteria severity were listed in four studies [ 78 , 99 , 100 , 102 ]; Risk was the most common level of severity in one study [ 100 ], while Injury was the most common in two studies [ 78 , 99 ], and Failure was the most common in one study [ 102 ]. Causes of sepsis were demonstrated in two studies [ 99 , 101 ]; in these studies, sepsis was caused by intrathoracic infections (such as pneumonia) and intra-abdominal infections in approximately 30 and 25% of cases, respectively, thus accounting for more than half of all cases.…”
Section: Cq4-2: Should Septic Aki and Non-septic Aki Be Discriminatedmentioning
confidence: 99%
“…In developing the present guideline, PubMed was used to identify papers which compared septic and non-septic AKI. Nine observational studies were identified [78,[98][99][100][101][102][103][104][105]; seven of these studies were prospective, while two were retrospective. One of these studies was a retrospective study by Bagshaw et al which utilized the Australian and New Zealand Intensive Care Society (ANZICS) database [78]; the study featured 14,039 septic AKI patients and 29,356 non-septic AKI patients, a prominently large number of patients compared to other studies.…”
Section: Commentarymentioning
confidence: 99%
“…One of these studies was a retrospective study by Bagshaw et al which utilized the Australian and New Zealand Intensive Care Society (ANZICS) database [78]; the study featured 14,039 septic AKI patients and 29,356 non-septic AKI patients, a prominently large number of patients compared to other studies. Seven studies compared in-hospital mortality [78,[98][99][100][101][102][103], while five studies compared ICU mortality [78,100,101,104,105].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation